A QUESTIONNAIRE-BASED STUDY TO ASSESS FEEDBACK ON CURRENT TEACHING-LEARNING METHODS AND THEIR OPINION FOR PERSPECTIVE CHANGES AMONG SECOND-YEAR MBBS STUDENTS - MUTHUKAVITHA, G.; R., KUMARAN; UMAMAHESHWARI, C. (International Journal of Current Pharmaceutical Research, 2026)
Objective: To collect and analyze feedback from second-year MBBS students about commonly used teaching-learning methods and to summarize their perspectives for potential changes. Methods: A validated 25-item questionnaire covering five domains (Assignments, Seminars, Small Group Discussions, Lectures, Self-Directed Learning) was administered to second-year MBBS students. Responses are recorded in a five-point Likert scale (Strongly Agree to Strongly Disagree) and were summarized with descriptive statistics. Results: Assignments, small group discussions and lectures received predominantly positive responses. Seminars showed moderate acceptance with varying neutrality, while self-directed learning elicited mixed responses, suggesting the need for clearer guidance and structure. Conclusion: A blended approach that retains high-quality lectures and assignments while expanding small group activities and improving the scaffold for self-directed learning is recommended.